Spin period evolution of the newly identified ULX pulsar (NGC 300 ULX1) associated with the supernova impostor SN2010da - Vasilopoulos, G.; Haberl, F.; Carpano, S.; Maitra, C. (2018)
Following the discovery of the newly discovered ULX pulsar in NGC 300 (ATel #11158) we searched the available X-ray data for the evolution of the spin period of the neutron star and the X-ray luminosity.
Keywords: Neutron Star; Pulsar